Marketing Margin Assesment Of Off-Season Vegetables Value Chain In Surkhetdailekh Road Corridor - Poudel, Prabin (Journal of Agriculture and Environment, 2013)
A study was carried out to identify structural causes of marketing margin for off-season vegetables value chain in a part of Surkhet-Dailekh road corridor during July to August 2011. Cost of production and producer's price were calculated at collection point of Bubairakhe in Goganpani VDC of Surket, and consumer's price observed at 30km far end market in Birndranagar municipalty of Surkhet. From the result of study, the marketing margin found doubled in all types of off-season vegetables value chain. The share of postharvest loss observed first most important factor for higher marketing margin, in tomato 42 percent and cauliflower 37 percent. However, it found third important factor in cabbage 28 percent. The profit margin kept by value chain actors, with contrasting in common perception, observed second important factor for increasing marketing margin in tomato 31 percent, cauliflower 28 percent and cabbage 44 percent. Hence, apposite attempts to reduce post-harvest loss in off-season vegetables value chain might be an important way for reducing marketing margin in off-season vegetables value chain. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 27-31 DOI: http://dx.doi.org/10.3126/aej.v13i0.7584